Mechanical and morphological properties of poly(3-hydroxybutyrate)/poly(3- hydroxybutyrate-co-3-hydroxyvalerate) blends - Conti D.S. (2006)
With the objective of developing new biodegradable materials, the mechanical properties and the morphology of blends of poly(3-hydroxybutyrate), P(3HB), and poly(3-hydroxybutyrate-co-3-hydroxyvalerate), P(3HB-co-3HV), were studied in this work. P(3HB) (492 kg · mol-1)/P(3HB-co-3HV)- 6%3HV (294.2 kg · mol-1) blends were prepared by injection in a wide range of proportions and characterized by mechanical behavior of tensile strength, Izod impact strength and hardness Shore D. According to the increase of the copolymer content in the blend, it was detected that the hardness Shore D and the maximum tensile strength presented a significant reduction, the elasticity modulus showed a significant reduction, the elongation at break presented a significant increase and the Izod impact strength practically remained constant. Scanning electronic microscopy (SEM) was carried out in the fractured surface of the samples obtained during the tests of tensile and impact strength. These analyses showed a morphology with fragile fracture for whole blends, agreeing with mechanical results previously reported. Copyright © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.